Open access solutions for biodiversity journals: Do not replace one problem with another - Peterson, A. Townsend (2019)
For much of the twentieth century, many or most scholarly journals in biodiversity, ecology, biogeography and conservation were owned and published by scientific societies and made available tothe broader scientific community at relatively low cost. However, the past several decades have seen a dominant process of commercialization of the publication process in this field, either by commercial publishing firms taking over publication of journals owned by a society (e.g., Evolution), or by commercial publishers starting new journals to fill "niches" that were until then empty in the scholarly publishing ecosystem. Diversity and Distributions is an example of this latter category of journals, having been created by Wiley Publishers in 1993 (as Biodiversity Letters). Being a journal owned by a commercial publisher, it has always been accessed by readers via subscription, but the publication process has been free to potentialauthors whose work has passed peer review. A recent announcement from Wiley Publishers on the Diversity and Distributions website, however, was as follows:We are pleased to announce that Diversity and Distributions will join the Wiley Open Access portfolio as of 1st January 2019, when all articles (includingthe entire back catalogue) will become free to read, download and share for all. This exciting development will place the journal at the forefront of open science in the community.This change would appear to be positive, as it would remove the for‐pay subscription barrier to reader access to the journal, and thus would appear to constitute an intriguing step in a series of advances in opening access to the scientific literature, in line with recent proposals as those of cOAlition S (https://www.scienceeurope.org/coalition-s/). However, the good news on the webpage is followed by a more ominous, "... all submissions received after 8th October 2018 will be subject to an Article Processing Charge (APC)." We have come to understand that these APCs will be US$2,200 per paper published, which is very expensive compared with the bulk of open access journals accessibleto ecology and conservation science